Helicobacter pylori Infection in Cirrhotic Patients With Portal Hypertensive Gastropathy: A New Enigma? - Alarfaj, Sumaiah J.; Abdallah Mostafa, Sally; Abdelsalam, Ramy A.; Negm, Walaa A.; El-Masry, Thanaa A.; Hussein, Ismail A.; El Nakib, Ahmed Mohamed (Frontiers in Medicine, 2022)
The relationship between Helicobacter pylori (H. pylori) infection and Portal hypertensive gastropathy (PHG) is still a debatable matter. The goal of this study is to find out how common H. pylori infection is in cirrhotic patients with PHG and to see if there's a link between H. pylori infection and PHG severity. Out of 340 cirrhotic patients who had upper Gastrointestinal Tract (GIT) endoscopy for early varices screening, 80 cirrhotic patients with PHG (cases) and 80 cirrhotic patients without PHG (controls) had repeated stomach biopsies for histological evaluation for the presence or absence of H. pylori infection. H. pylori was found in 44 cirrhotic patients (55%) who had PHG (cases), compared to 22 cirrhotic patients (27.5%) who did not have PHG (controls). In patients with PHG, the risk assessment revealed a significant prevalence of H. pylori infection (P< 0.001). 27 individuals with severe PHG, 9 patients with moderate PHG, and 8 patients with mild PHG were among the 44 patients with PHG and positive H. pylori infection. In patients with negative H. pylori infection, mild PHG was found in 33 patients and three patients were found to have moderate PHG (P< 0.001) which indicated that the difference was statistically significant. PHG severity was considerably reduced in patients who tested positive for H. pylori before and after treatment (P <0.001). In patients with PHG, the prevalence of H. pylori infection is much higher. PHG is more common in patients with H. pylori infection. To improve PHG severity in cirrhotic individuals, H. pylori infection must be eradicated.